On the measurement and interpretation of health inequality, income inequality, and income-related health inequality - Walli-Attaei, Marjan (My University, 2018)
Governments, international agencies, and researchers routinely assess health and income inequalities and inequities so as to better communicate the evidence of their levels and trends to both policy-makers and the general public. Measuring the extent to which differences in health or income are unequal or unfair is, however, complex. This thesis contains three chapters centrally concerned with inequalities, though the focus differs across chapters. Chapter 2 helps address the gap between the requirements of indices often used for measuring income-related health inequality and current research practice by providing a non-technical review and critical assessment of the recent literature. This chapter should function as a guide for policy researchers and analysts to help them be more critical consumers of studies that use these indices while also helping applied researchers in choosing inequality measures that have the normative properties they seek. Most measures of inequality make assumptions about the extent to which society is averse to inequality. Moreover, analysts often assume that attitudes toward inequalities in health or income are the same. Chapter 3 is the first study using a mixed-methods approach to assess public attitudes toward inequalities in income, health, and income-related health inequality to determine preferences and how attitudes toward inequalities in these domains differ. Chapter 2 and 3 contribute to a greater understanding of the measurement and interpretation of inequalities. While chapters 2 and 3 focus on inequalities among individuals within a society, chapter 4 focuses on inequalities globally among societies. Chapter 4 examines global health inequalities that result from medical care use using the example of long-standing drug technologies for treating hypertension. The study links availability and affordability of blood-pressure-lowering medicines with individual use and health outcomes. Chapter 4, therefore, provides an empirical illustration on how country-specific policies can play an important role in either countering or exacerbating health differences.
Essays on Health, Inequality and Fairness
Keywords: health inequality; income inequality; socio-economic-related health inequality; stated preference experiment; concentration-based indices; inequality aversion